Multimedia Sebagai Metode Variatif dalam Meningkatkan Motivasi Belajar Akidah Akhlak di Masa Pandemi - Mukhlishotin (CV. Gerasi Insan Nusantara, 2021)
Akidah Akhlak competence is one of the sub-subjects of Islamic religious education which in the learning process can be done through guidance, teaching, training and experience. The emphasis on learning the moral aqidah is not just on mastering knowledge, but most importantly how to raise awareness of students having a strong faith and noble character which is manifested in daily behavior. The purpose of learning the Akidah Akhlak subject is to instill and increase students’ faith and increase awareness for noble character. The formulation of the problem in this study is: Is there an increase in learning motivation after the application of varied methods with multi-media in learning akidah Akhlak. The approach used in the research is a quantitative approach, with the type of action research. Researchers are directly involved in the research from the beginning to the end of the research. Researchears try to see, observe, feel, appreciate, reflect and evaluate the ongoing learning activities. The stages of stages of action research implementation consist of planning (planning), implementation (acting), observation (observing), and reflection (reflecting). To get accurate research results, the data that has been collected is analyzed statistically by using the mean or average formula. Referring to the action hypothesisi proposed in this classroom action research, it can be concluded that: there is an increase in learning motivation in the Akidah Akhlak fiel of study after the application of varied methods with multi-media on akidah Akhlak learning in students at MTsN 7 Kediri.